Preoperative chemotherapy usage experience for intrahepatic cholangiocarcinoma - A. N. Polyakov; D. A. Granov; Yu. I. Patyutko; I. A. Pokataev; A. A. Polikarpov; T. I. Kagacheva; I. S. Bazin; A. Sh. Umirzokov; D. Yu. Frantsev; V. N. Zhuikov; D. V. Podluzhny (Исследования и практика в медицине)
Purpose of the study was to evaluate the safety and feasibility of preoperative chemotherapy in intrahepatic cholangiocarcinoma (IHCC).Patients and methods. A total of 171 liver resections for IHCC were performed between 2007 and 2021, of which 24 were preceded by preoperative therapy (14.0 %). Systemic therapy was conducted in 11 patients (45.8 %). Regional chemotherapy was provided to 13 patients (54.2 %). In two cases, regional chemotherapy was supplemented with systemic therapy.Results. A significant increase in the proportion of patients with clinical stage IIIb and higher was observed in the group of patients who had received preoperative therapy (83.3 % vs. 35.4 %, p < 0.0001). Complications of preoperative therapy occurred in 45.8 % of patients, with grade three and above complications identified in three patients (12.5 %). The incidence of postoperative complications (37.5 % vs. 42.9 %, p = 0.79), post‑resection liver failure (8.3 % vs. 13.6 %, p = 0.7) and postoperative mortality (4.2 % vs. 3.4 %, p = 0.68) in the preoperative therapy group were similar to those in the control group. The rate of radical resections was also identical, 83 % in both groups (p = 0.8). The relapses rates within the first six months after the surgery were similar: 25 % of patients in both groups (p = 0.62). The median OS reached 36 months in the main group and 32 months in the control one (p = 0.81).Conclusion. Since the main group predominantly included patients with more advanced stages of the disease and yet the treatment resulted in comparable immediate and long‑term outcomes, it can be concluded that preoperative therapy can be justified in patients with IHCC who have factors predisposing to poor prognosis. Randomized trials are necessary to determine the rationality, as well as the type and regimen of preoperative therapy to be used in patients with IHCC.